Pride and prejudice of legal imperialism with reference to presevering English law in Malaysia: making sense the doctrines of reception and subsequent attraction - Ramalingam, Chithra Latha; Ali Mohamed, Ashgar Ali (CLJ Publication, 2020)
The benefit of the British Empire was that by the 18th Century, English Law was already well settled in the Malay Peninsular and it was relatively easy to determine which laws that can be received and applied. In light of the above, this chapter reviews the history of English law in Malay Peninsular with special focus on why the need to review ss. 3 and 5 of the Civil Law Act 1956, which relates to the current application of English Law in Malaysi